Drosophila head segmentation factor buttonhead interacts with the same TATA box-binding protein-associated factors and in vivo DNA targets as human Sp1 but executes a different biological program. - Schock, F.; Sauer, F.; Jackle, H.; Purnell, B.A. (Proceedings of the National Academy of Sciences of the United States of America, 1999)
The Drosophila gene buttonhead (btd) is required for the establishment of three embryonic head segments. It encodes a zinc-finger-type transcription factor expressed in the corresponding head segment anlagen in the blastoderm stage embryo. The DNA-binding properties of the btd protein (BTD) are indistinguishable from the human transcription factor Sp1. Furthermore, BTD and Sp1 are capable of activating transcription in transfected cultured cells through interaction with the same DNA target sites. Herein we show that BTD and Sp1 functionally interact with the same TATA box-binding protein-associated factors and support in vitro transcription activation through these contacts. Transgene expression of BTD results in the rescue of the head segments that fail to develop in btd mutant embryos, whereas Sp1 or Sp1 containing the zinc finger region of BTD rescues mandibular segment development. The results suggest that BTD contains functional domains other than an equivalent DNA-binding region and interaction sites of the TATA box-binding protein-associated factors, which are necessary to establish head segments that fail to develop in response to Sp1.